Rancang Bangun Aplikasi Pembelian Tiket Berbasis Web Pada PT Sri Varia Wisata - Indriani, Sephia; Arman, Molavi (Jurnal Teknologi Sistem Informasi, 2024)
PT Sri Varia Wisata or known as Varita is a company engaged in the business of travel agency services, this company is a subsidiary of PT Pupuk Sriwidjaja or better known as Pusri which is under the auspices of the Pusri Employee Welfare Foundation (YKPP). The purpose of making this application is to help the ticketing section work more easily and efficiently in ticket purchase transactions at PT Sri Varia Wisata. Data collection techniques used are the stages of planning, analysis, design, coding and testing. The development of this system uses an iterative method. To describe the proposed application using Entity Relationship Diagrams, Data Flow Diagrams and Context Diagrams. Making this application using the PHP programming language and ticket sales database using MySQL. Users of this information system are the head office, ticketing staff and customers of PT Sri Varia Wisata. The conclusion obtained is that with this application, both ticketing staff and customers can be facilitated in conducting ticket sales transactions and can make it easier for the head of the office to find out the history of ticket sales in real time.